(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This article explores Scenario-Based Learning (SBL) as a transformative approach in language education, emphasizing its constructivist roots and practical relevance. It highlights how SBL techniques - such as role-playing, decision-making, problem-solving, and interactive storytelling - immerse students in authentic, dynamic situations that mirror real-world communication challenges. By fostering critical thinking, collaboration, and adaptability, SBL moves beyond traditional language instruction, promoting fluency through experiential learning. The discussion underscores SBL’s effectiveness in preparing learners, particularly future educators, for real-life language use in professional and everyday contexts.